Coulomb explosion imaging of polyatomic molecules with femtosecond optical and XFEL pulses - Chen, Keyu (My University, 2025)
Light-induced chemical reactions are essential processes that have a profound impact on various aspects of human life and technology. A prime example is photosynthesis, where photons from sunlight drive the conversion of water and carbon dioxide into oxygen and glucose, supporting vital life processes. Similarly, light-induced molecular dynamics are at the heart of photovoltaic technologies, which convert photon energy into electrical energy, providing a key energy source. Additionally, extensive research and practical applications exist in the field of molecular and biomolecular switches, where, among other applications, photons are employed to regulate enzyme activities. From a broader perspective, animals and humans can also be seen as undergoing a form of photosynthesis, as we produce vitamin D3 in our skin when exposed to sunlight. The photochemical reaction involving the ring opening in the 1,3-cyclohexadiene molecule serves as a model system for the photosynthetic process of pre-vitamin D generation. A thorough understanding of photo-induced molecular dynamics is essential for advancing our knowledge of these phenomena and enhancing our technological capabilities. Capturing such dynamics in real time has long been a challenge due to the ultrafast (femtosecond) timescales on which many fundamental chemical processes, including bond breaking, isomerization, and ring conversion, occur. Recent advancements in ultrafast spectroscopies and the development of intense light sources, from table-top optical lasers to X-ray free-electron lasers (XFELs), have enabled researchers to visualize these ultrafast dynamics in real time, acquiring a sequence of timed snapshots of evolving molecular structures. Among the most promising techniques for such ‘molecular movie making’ is the so-called Coulomb Explosion Imaging (CEI), which reveals molecular structures by rapidly ionizing molecules to highly charged states and detecting the momenta of the resulting ion fragments. When implemented in a pump–probe configuration, where a pump light pulse initiates a reaction and a delayed probe pulse maps it with Coulomb explosion, CEI can provide unique insights into the evolution of molecular geometries on ultrafast timescales. A successful application of the CEI technique to studies of polyatomic systems relevant to chemistry requires a detailed understanding of the fragmentation processes involved in the formation of Coulomb explosion patterns and of the observables involved in their formation. The main goals of this thesis are (i) to explore such fragmentation dynamics in a few model systems, (ii) to gain detailed understanding of the mechanisms involved in the laser-driven CEI, (iii) to develop efficient routines for handling and representing multidimensional CEI observables, and (iv) to use the developed procedure and the knowledge gained to image light-driven ring conversion reactions. This thesis aims to investigate three different model systems. First, it focuses on the CEI of ethylene (C₂H₄) driven by intense femtosecond near-infrared laser pulses. Ethylene, a typical unsaturated hydrocarbon molecule, represents an attractive model system for CEI of polyatomic molecules because of its relative simplicity, accessibility for theory, and its planar geometry in the ground state of the neutral molecule. At the same time, it has enough complexity for studying different multi-particle breakup channels, particularly those involving one or more of the four hydrogen atoms, whose detection is one of the important capabilities of the CEI technique. The experimental results and detailed simulations presented here reveal and characterize competing concerted and sequential mechanisms involved in the formation of Coulomb explosion patterns for a triply charged molecule, disentangle two different four-body breakup pathways for quadruple ionization (‘cis-’ and ‘trans-fragmentation’), and explore possibilities and challenges for CEI relying on full atomization of the molecule (breakup into six atomic ions). As a second model system, this thesis addresses CEI of 2(5H)-thiophenone (C₄H₄OS) employing intense femtosecond laser and XFEL pulses. Here, we first present static CEI patterns for this molecule obtained with 2.6 keV X-ray pulses at the European XFEL and with table-top near-infrared lasers. The results show that a three-dimensional structure of such a complex, non-planar system can be mapped using CEI, including the 3D arrangement of its hydrogen atoms. While the data obtained with XFEL pulses ionizing the sulfur K-edge are more robust and exhibit much higher signal to noise ratio, the same signatures of the 3D molecular structure can still be revealed in the experiments with near-infrared lasers when using appropriate data analysis procedures. As a second step, we apply laser-driven CEI to image ring opening in 2(5H)-thiophenone triggered by the absorption of an ultraviolet (UV) photon. The CEI patterns map the femtosecond evolution of this ring opening reaction, complementing earlier results obtained with time-resolved photoelectron spectroscopy and ultrafast electron diffraction. Finally, we perform detailed simulations of the CEI of ring conversion dynamics in the 2,3-dihydrofuran (C₄H₆O) molecule upon deep-UV excitation and present the first experimental results demonstrating the feasibility of mapping this photoreaction with CEI employing table-top near-infrared lasers. Overall, this thesis demonstrates the capability of CEI to image molecular structures, track ultrafast dynamics across a range of systems, and provides several essential recipes for understanding and representing multidimensional CEI data. These findings contribute to the broader understanding of photo-induced molecular reactions and provide a foundation for future studies of ultrafast photochemical processes.
Keywords: Ultrafast molecular dynamics; Coulomb explosion imaging; Femtosecond lasers; Strong field ionization; X-ray Free-electron lasers